Mushrooms from cotton - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1993)
The Tekoa Mushroom farm in Israel has developed a way of pulverizing cotton stalks and turning them into a suitable substrate for mushroom growing. High powered machines are required because the stalks are tough, but new machines with lower power...